Ecoambiguity and tourism development in contemporary Vietnam – case study of an ethnic Khmer village in southern Vietnam (Revista de Investigaciones Universidad del Quindío, 2021)
Many development projects in Vietnam today, including tourism, are partially focused on ecology. However, the mentality of cultivating for later gains is still popular. In addition to the goal of creating opportunities to benefit local communities, this development discourse conveys a sense of ‘ecoambiguity’. This study mainly applies the concept of "ecoambiguity" of Thornber (2012) to discuss the current situation and impact of tourism activities in the Khmer community around Bà Om Pond in Trà Vinh, Vietnam. Unlike previous works that discussed the beauty and value of Khmer religion, temples, rural life, festivals, and art, this research argues that people-centered policies have never enabled people to achieve their goals.
Keywords: tourism; development discourse; Khmer; Bà Om Pond; Trà Vinh